Continuous Subcutaneous Insulin Infusion Initiation Is Associated With Blood Pressure Reduction in Adults With Type 1 Diabetes. (July 2019) - Markakis, Konstantinos; Alam, Tayiba; Jinadev, Pushpa; Chapman, Alyson; Urwin, Andrea; Thabit, Hood; Boulton, Andrew J. M.; Rutter, Martin K.; Leelarathna, Lalantha
Background: In type 1 diabetes (T1D) continuous subcutaneous insulin infusion (CSII) use has been associated with lower risks for mortality and diabetes-related complications when compared to multiple daily injections. There are limited data on the effect of CSII on blood pressure (BP). We aimed to evaluate the relationship between CSII initiation and BP changes. Methods: We performed a retrospective, single-center, observational study including all adults with T1D who initiated CSII between 2001 and 2014. Mean systolic BP levels were calculated from values obtained up to 15 months before and up 15 months after CSII initiation. Results: We studied 436 adults (46% male; mean [95% CI] age: 45 [36, 54] years, duration of diabetes: 20.3 [19.1, 21.5] years). CSII was associated with the following changes (post minus pre CSII levels) in mean (95% CI) SBP and DBP levels, respectively: whole cohort (N = 436): −2 (−1, −3), P < .001 and −2 (−1, −2), P < .001; those taking stable antihypertensive medication (n = 118): −4 (−6, −2), P < .001 and −2 (−3, −1), P < .001; antihypertensive treatment-naïve patients (n = 279): −1 (−2, 0), P = .147 and −1 (−2, 0), P = .002. In multivariate regression analysis including age, sex, diabetes duration, pre-CSII BP, HbA1c and weight changes, only pre-CSII BP showed an independent association with BP drop in all patients' groups. Once adjusted for pre-CSII BP there was no significant difference between those on antihypertensive drugs and antihypertensive treatment-naïve individuals. Conclusions: We showed BP reduction in association with CSII therapy particularly in those on antihypertensive medication. These original findings may partly explain the cardiovascular and mortality benefits associated with CSII therapy.